2011
DOI: 10.1002/bem.20690
|View full text |Cite
|
Sign up to set email alerts
|

Do people with idiopathic environmental intolerance attributed to electromagnetic fields display physiological effects when exposed to electromagnetic fields? A systematic review of provocation studies

Abstract: Idiopathic environmental intolerance attributed to electromagnetic fields (IEI-EMF) is a controversial illness in which people report symptoms that they believe are triggered by exposure to EMF. Double-blind experiments have found no association between the presence of EMF and self-reported outcomes in people with IEI-EMF. No systematic review has assessed whether EMF exposure triggers physiological or cognitive changes in this group. Using a systematic literature search, we identified 29 single or double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 42 publications
1
57
0
1
Order By: Relevance
“…Currently, it is not feasible to determine the remote health effects that, advisably, should be followed-up in prospective studies. Conclusions of the review of provocation studies by Rubin et al (2011) suggest that electromagnetic fields are not the reason of health problems among people with electromagnetic hypersensitivity [24]. However, we cannot directly compare the results of our study with those data because we performed a survey among people from general population, and not among people with idiopatic environmental intolerance atrributed to electromagnetic fields [24].…”
Section: Discussionmentioning
confidence: 78%
“…Currently, it is not feasible to determine the remote health effects that, advisably, should be followed-up in prospective studies. Conclusions of the review of provocation studies by Rubin et al (2011) suggest that electromagnetic fields are not the reason of health problems among people with electromagnetic hypersensitivity [24]. However, we cannot directly compare the results of our study with those data because we performed a survey among people from general population, and not among people with idiopatic environmental intolerance atrributed to electromagnetic fields [24].…”
Section: Discussionmentioning
confidence: 78%
“…Regarding intolerance to EMFs, provocation studies have shown that the EMF source per se does not seem to cause physiological symptoms and reactions (Rubin et al, 2011). These individuals may to a larger extent pay attention to environmental factors in general and react with stress responses, resulting in physiological symptoms that are attributed to factors in the environment.…”
Section: Discussionmentioning
confidence: 95%
“…SBS is defined as a set of mucosal, skin and general symptoms that are related with residing or working in a particular building with certain environmental problems (Burge, 2004). Electrosensitivity is a condition in which sufferers experience diverse, non-specific symptoms when exposed to weak electromagnetic fields from sources such as computer equipment or mobile phones (Rubin et al, 2011). NS is described as a general hypersensitivity to normal environmental sounds of any frequency that are not threatening nor uncomfortably loud to a typical person (Baguley, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies showed differential changes in cognitive function and structure between individuals. In populations, the prevalence of self-reported electromagnetic hypersensitivity has usually been attributed to somatization disorders [11,12]. A possible nonpsychological basis for electromagnetic hypersensitivity was evidenced by the occurrence of field-onset and field-offset brain potentials [13], and the induction of steadystate changes in brain electrical activity that persisted in the presence of the field [14], but the mechanism is still not clear.…”
mentioning
confidence: 98%